Dynamics of the Social Skills Formation in Primary Schoolchildren with Intellectual Disabilities studying in Different Learning Conditions - Elena BORISOVА; Irina KOZINA; Tatyana KARANDAEVA; Nadezhda POLYAKOVA; Nataliya KOMOVA (Communications of International Proceedings, 2021)
The article presents the results of a study of the development of social skills in primary school children with intellectual disabilities, studying in different conditions, and highlights general and specific characteristics. The necessity of purposeful psychological and pedagogical influence is determined, taking into account the specifics of the interaction of psychopathological and environmental factors.
Keywords: Socialization; social skills; life competencies; primary school children with intellectual disabilities; inclusive education.